Glucagon receptor family in GtoPdb v.2021.3. (2021) - Bataille, Dominique; Chan, Susan L.; Delagrange, Philippe; Drucker, Daniel J.; Göke, Burkhard; Hills, Rebecca; Mayo, Kelly E.; Miller, Laurence J.; Salvatori, Roberto; Thorens, Bernard
No abstract available